Stigma: A Barrier in Supporting Nurse Well-Being During the Pandemic - Weston, Marla J.; Nordberg, Allison (Nurse leader, 2022)
Public media and the nursing literature are replete with data and anecdotal stories evidencing the overwhelming impact to nurses’ well-being during the COVID-19 pandemic. Although many organizations have rallied and are providing robust services to support nurses through the pandemic, stigma (negative perceptions, attitudes, and discrimination) about mental health support is contributing to nurses’ reluctance to use the many resources available to them. This article outlines strategies for reducing the stigma and eliminating the barriers associated with obtaining the mental and emotional well-being support and services that nurses need and deserve.